Boron, Nitrogen-Doped Porous Carbon Derived from Biowaste Orange Peel as Negative Electrode Material for Lead-Carbon Hybrid Ultracapacitors. Issue 9 (6th April 2020) - Muduli, Sadananda; Naresh, Vangapally; Martha, Surendra K.
Abstract : Lead-Carbon hybrid ultracapacitors have attracted attention in recent times due to high power density and remarkably long cycling stability. Herein, we report bio-waste orange peel derived B, N doped porous carbons as negative electrode active material for Pb-C hybrid ultracapacitors. B, N doped porous carbons are obtained from orange peel using boric acid by carbonization at 800 °C. B, N doped porous carbons contain about 1.22% of boron, 2.89% of nitrogen. These porous carbons exhibit 866 F g −1 capacitance at 1 A g −1 current density in potential range between the −0.4 V to 0.2 V. Pb-C hybrid ultracapacitors assembled with these carbons as the negative electrode and in situ formed PbO2 as a positive electrode can deliver capacitance of 192 F g −1 at 10 A g −1 and stable over 10, 000 cycles. The superior electrochemical performance of lead-carbon ultracapacitor is due to the boron and nitrogen doping into the carbon, which increases the hole density and electron carrier, respectively and subsequently enhances the charge storage property. The significant improvement in capacitance of the ultracapacitor electrode of Pb-C hybrid ultracapacitors presented here opens up a new realm of possibilities for the lead-carbon ultracapacitor development and will contribute directly towards improving the energy and power density of the system.